2020
DOI: 10.1186/s40648-020-00156-3
|View full text |Cite
|
Sign up to set email alerts
|

Verbal guidance for sit-to-stand support system

Abstract: Artificial intelligence (AI)-based robots have become popular in various fields, thereby increasing the demand for care robots. Such care robots recognize or estimate factors such as human states and then perform actions depending on the estimation results. If the humans cooperating with robots do not understand robot functions well, the task will not be performed appropriately. Additionally, it is possible that the estimation may be incorrect. Robots may make mistakes, and there is a risk that these mistakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In addition, because the robot will stop and return to its original position when it detects an anomaly, the announcement of the stop, the announcement that "It will back up," and the countdown it executes before moving the armrest clearly declare the next action of the robot so that the user can respond to an anomaly with a sense of ease. In a previous study [17], presenting information via a speaker while the user is standing up was found to have a significant impact on the sense of ease and usability of the robot. However, experiments to support standing up, walking, and sitting down, including anomalies found during those movements, in combination with visual information presented on a display were not conducted.…”
Section: Sittingmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, because the robot will stop and return to its original position when it detects an anomaly, the announcement of the stop, the announcement that "It will back up," and the countdown it executes before moving the armrest clearly declare the next action of the robot so that the user can respond to an anomaly with a sense of ease. In a previous study [17], presenting information via a speaker while the user is standing up was found to have a significant impact on the sense of ease and usability of the robot. However, experiments to support standing up, walking, and sitting down, including anomalies found during those movements, in combination with visual information presented on a display were not conducted.…”
Section: Sittingmentioning
confidence: 92%
“…By presenting the robot's actions, timing, and other information on a visual interface and through speakers, the robot will be theoretically easy to use and generate a sense of ease. The robot's actions and the user's next move are useful information that can be presented to the user [8], and audio presentation of the timing of the actions has proven to be effective [17]. Therefore, we designed the display to show the current state and next move of the user and robot on the screen, and set up the audio to announce the timing and the user's move.…”
Section: Knowledge Representation Interfacementioning
confidence: 99%
“…Many efforts have investigated using robots for assisting seniors to stand and walk on their own, which is a major goal of Humanitude ( Martins et al, 2012 ; Cifuentes and Frizera, 2016 ; Geravand et al, 2017 ; Ferrari et al, 2020 ; Takeda et al, 2020 ). Robotic technologies do already exist that facilitate the standing or walking of PwDs by themselves.…”
Section: Technical Challenges Toward Artificial Systems That Incorporate Humanitude Techniquesmentioning
confidence: 99%
“…For example, Takeda et al proposed a sit-to-stand support system that informed users by verbal guidance when assistance will begin. Healthy adult users felt comfortable when the start of the robot’s movement was indicated by voice ( Takeda et al, 2020 ), although they did not evaluate their system with healthy seniors or PwDs. Providing a feeling of comfort through multimodal information in standing and walking is critical for PwDs.…”
Section: Technical Challenges Toward Artificial Systems That Incorporate Humanitude Techniquesmentioning
confidence: 99%
“…The diversity of explanations can be exemplified by the life story book, which Setchi et al [44] suggest for reminiscence therapy by robots. Another example is verbal guidance for a sit-to-stand support system [46].…”
Section: Previous Researchmentioning
confidence: 99%